MUC5AC and inflammatory mediators associated with respiratory outcomes in the British 1946 birth cohort. Issue 6 (25th July 2013) - Johnson, Lauren; Shah, Imran; Loh, Andrew X.; Vinall, Lynne E.; Teixeira, Ana S.; Rousseau, Karine; Holloway, John W.; Hardy, Rebecca; Swallow, Dallas M.
Abstract Background and objective Dysregulation of respiratory mucins, MUC5AC in particular, has been implicated in respiratory disease and MUC5AC expression is up‐regulated in response to environmental challenges and inflammatory mediators. The aim of this study was to examine the effect of genetic variation on susceptibility to common respiratory conditions. Methods The association of MUC5AC and the closely linked genes MUC2 and MUC5B with respiratory outcomes was tested in the MRC National Survey of Health and Development, a longitudinal birth cohort of men and women born in 1946. Also examined were the functional variants of the genes encoding inflammatory mediators, IL13, IL1B, IL1RN, TNFA and ERBB1, for which there is a likely influence on MUC5AC expression and were explored potential gene–gene interactions with these inflammatory mediators. Results Statistically significant associations between the 3'ter MUC5AC simple nucleotide polymorphism (SNP) rs1132440 and various non‐independent respiratory outcomes (bronchitis, wheeze, asthma, hay fever) were reported while the adjacent loci show slight (but largely non‐statistically significant) differences, presumably reflective of linkage disequilibrium (allelic association) across the region. A novel association between bronchitis and a non‐synonymous functional ERBB1 SNP, rs2227983 (aka epidermal growth factor receptor:R497K, R521K) is also reported and evidence presented of interaction between MUC5AC and ERBB1 and between MUC5AC and IL1RN with respect to bronchitis. The ERBB1 result suggests a clear mechanism for a biological interaction in which the allelic variants of epidermal growth factor receptor differentially affect mucin expression. Conclusions The MUC5AC association and the interactions with inflammatory mediators suggest that genetically determined differences in MUC5AC expression alter susceptibility to respiratory disease.